THE LEGAL PERSPECTIVE ON THE ILLEGALITY OF THRIFTING BUSINESSES IN INDONESIA - Atha Hukama Ardyawati; Effi filipia Fronica Irawan; Gina Amelia; Jessen Aprillian; Vanesa Felicia Prayogo (Problematika Hukum, 2021)
Thrifting is the act of purchasing second-hand items, considered a cost-saving measure by buyers. The thrifting phenomenon is not new but has regained popularity among the Indonesian community. The rapid evolution of fashion and the emergence of new trends in a short period make thrifting an attractive choice for individuals who aspire to appear stylish. The allure of thrifting lies in the diverse range of fashion models, typically rare and offered at affordable prices. Therefore, many individuals in Indonesia are inclined to venture into the thrifting business due to its current popularity and the substantial income it generates. This phenomenon captures the attention and provides a strong basis for researchers to delve further into information regarding illegal thrifting activities in Indonesia. Additionally, the researchers conduct further exploration on business permits for thrifting from the government, the existence of Intellectual Property Rights (HKI), and the standards for the quality of traded goods. The researchers employ a qualitative approach with literature study techniques and analysis.Keywords: Business; Fashion; Import; Thrifting